Conflict Management Strategies in Vocational Education: A Qualitative Case Study of a Faith-Based School in Indonesia - Samsilayurni Samsilayurni; Nurlena Nurlena; M. Ilham Fikriawan (STAI Hubbulwathan Duri, 2026)
Interpersonal conflict between teachers and students is a common phenomenon in vocational schools, where diverse student backgrounds, academic pressure, and practice-oriented learning create complex interaction dynamics. Although conflict management in educational settings has been widely studied, limited research has examined how religious values shape conflict resolution strategies in faith-based vocational schools. This study investigates forms of teacher–student conflict and analyzes how Islamic values influence conflict management practices at SMK Muhammadiyah I Palembang, Indonesia. This study employed a qualitative case study design. Data were collected from 15 participants, including students, teachers, the principal, guidance and counseling (BK) staff, and a parent. In-depth interviews, participatory observations, and document analysis were conducted. Data were analyzed using Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing, with triangulation of sources and methods to enhance validity. Findings indicate that the dominant conflict management strategies are collaboration and accommodation. Conflicts commonly arise from disciplinary issues, communication misunderstandings, academic pressure, and differences in values. Resolution processes emphasize dialogue, deliberation (musyawarah), and mutual understanding, supported by active mediation from BK staff and parental involvement. Islamic values such as patience, mutual respect, and moral responsibility function not only as ethical principles but also as operational frameworks guiding mediation and reconciliation. The integration of religious values strengthens relationship-oriented conflict management, fostering constructive resolution, character development, and a conducive learning environment. The study highlights the importance of contextualizing conflict management theory within faith-based educational settings.